∫x*((e^x)^2)*dx第一换元法
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/03 18:01:41
∫x*((e^x)^2)*dx第一换元法∫x*((e^x)^2)*dx第一换元法∫x*((e^x)^2)*dx第一换元法原式=∫x*e^2xdx=∫xd(e^2x)/2=(x*e^2x)/2-∫(e^
∫x*((e^x)^2)*dx第一换元法
∫x*((e^x)^2)*dx第一换元法
∫x*((e^x)^2)*dx第一换元法
原式=∫ x*e^2x dx =∫ x d (e^2x)/2 =(x*e^2x)/2 - ∫ (e^2x)/2 dx =(2x*e^2x - e^2x)/4+C
用分部积分法,第一类换元法好像不行的
∫x*((e^x)^2)*dx是不是∫x[e^(x)^2]dx?
若是,则
∫x[e^(x)^2]dx=(1/2)∫2x[e^(x)^2]dx
=(1/2)∫[e^(x)^2]d(x^2)
=(1/2)∫e^tdt
=[e^t]/2+C
=[e^(x^2)]/2+C
∫x*((e^x)^2)*dx第一换元法
∫e^(-x)·dx 用第一换元法.
∫[dx/(e^x(1+e^2x)]dx
∫ e^(x^2)dx
∫X^2 e^-X^3 dx.
∫【x(cosx+e^2x)dx】
积分 ∫(e^x)/(x+2)dx
∫(x/2+e^x+sinx)dx
∫2^X e^X DX
∫x^3*e^x^2dx
∫ e^x-e^(-x)dx=e^x+e^(-x)|=e+1/e-2
∫(e-e^x)dx
∫ e^x / x dx
∫dx/[e^(2x)+e^(-2x)+2]
求不定积分∫[e^(2x)-3/e^x]dx
求不定积分∫(e^(2x)-1) / e^x dx
求不定积分∫e^2x * cos e^x dx
∫e^2x/3+e^4x dx